Urgensi Program Pelatihan Parenting dalam Meningkatkan Kemampuan Komunikasi Orangtua dengan Anak - Adiyati Fathu Rosonah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2019)
Abstract: This article presents a study of the urgency of parenting training programs in improving communication skills of parents with children based on the results of research and literature review. At present in Indonesia parenting training programs are not yet fully integrated into children's education programs in schools. The study of parenting training programs has also not been widely carried out in the context of developing countries. However, empirical evidence from various results of research and literature studies has proven that parenting training programs provide significant benefits in improving the quality of childcare including improving parent-child communication skills. Considering the importance and benefits, this program needs to be continually initiated and facilitated as a manifestation of microsystem synergy between home and school to ensure the optimization of child development.